Development Paradigm And Environmental Damage: A Review Of Islamic Ecoteology On Indonesia's Ecological Crisis - Ageng Widodo; Laeli Muflikhah , Laeli (Socio Religia, 2025)
Study This examine crisis Indonesian ecology as consequence from paradigm development extractive at a time evaluate its relevance with perspective Islamic ethics. With use approach studies library, research This explore literature related crisis forest, degradation ecological, development sustainable, and Islamic moral principles such as khalifah fil ardh, mizan, and ban fasad. Study results show three points main. First, the crisis ecology, especially deforestation and degradation forest secondary, causing pressure significant to diversity biological at a time conflict socio-ecological for public local. Second, development extractive and weak implementation formal policy affirms the need empowerment public as agent conservation through forestry social and management forest based community. Third, perspective Islamic ethics strengthens dimensions normative, emphasizing not quite enough human moral responsibility in guard balance ecological and social research​ This conclude that integration empowerment society, technical strategies, and Islamic moral values become key For development ethical sustainability​ at a time strengthen resilience socio-ecological local.